Implementation of enhanced recovery after surgery- ERAS, a paradigm shift in surgery - Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2018)
The history of enhanced recovery after surgery (ERAS) has its roots to the earlier ERAS Study Group. This was a collaborative group on peri-operative care to further develop ideas put forth in the 1990’s by Professor Henrik Kehlet of University of Copenhagen. Kehlet reported that the morbidity, mortality and overall costs of surgery requires multimodal interventions to reduce pain; cardiopulmonary, infective and thromboembolic complications; cerebral dysfunction; nausea and gastrointestinal paralysis, fatigue and prolonged recovery. The ERAS Society, registered and based in Stockholm, has over the years developed ‘perioperative care’ strategies to improve recovery after surgery through research, education, audit and implementation of evidence-based practice. An evidence-based consensus protocol for patients undergoing colon surgery was developed and published by the ERAS Study Group3 and later the group showed that just a protocol was not sufficient to change surgical practice in accordance with ERAS. The ‘manual of fast track recovery for colorectal surgery (Springer)’ was published by the ERAS Society as 1st in the series of enhanced recovery. Thereafter various professional societies and organizations around the world have worked together to develop, modify, promote and propagate ERAS. From its original work on colorectal surgery, the ERAS is now implemented in virtually all the disciplines of surgeries and the guidelines are available at ERAS Society website.The strategies of ERAS is designed for ‘preoperative, intraoperative and postoperative care’ through multimodal, integrated, multidisciplinary approach from all the stake holders: the patient, surgeons, anaesthesiologists, pain specialists, nursing staff, physical and occupational therapists, social services, and hospital administration. It advocates of the standardized medical care to improve the outcomes and lower the health care costs by minimizing surgical trauma, postoperative pain, complications, length of hospital stay, while expediting recovery and improving the overall outcomes.